Safety and efficacy of substance-based medical devices: Design of an in vitro barrier effect test - Bassetto, Rebecca; Perin, Stefano; Amadio, Emanuele; Zanatta, Samuele; Nenzioni, Davide; Bertin, Walter (Frontiers in Drug Safety and Regulation, 2023)
This study aims to develop in vitro barrier effect test over biomimetic membrane, useful to establish the film forming ability of a Substance-Based Medical Device (SB-MD). The method contemplates a multiparametric approach including: i)the measurement of the transmembrane passage of a molecular-like marker over an lipid-impregnated biomimetic membrane (simulating the skin, gastro-intestinal and buccal tissues) by using a static diffusion cells apparatus(Franz Cells); ii)the evaluation of the integrity of the membrane (colorimetric test). In a first step, a series of lipid-impregnated biomimetic membranes (simulating gastro-intestinal, buccal and the skin tissues) were implemented and their permeability performance validated using model drugs (caffeine and acyclovir), by referring to literature’s data. As result, the apparent permeability(Papp) of caffeine over the biomimetic gastro-intestinal membrane(Papp=30.5E-6cm/s)were roughly comparable to literature’s values obtained with Caco-2 cell line membrane(Papp=30.8E-6cm/s)and with Franz cell method(Papp=36.2E-6cm/s). Acyclovir, resulted to be a poorly permeable substance both in literature and experimental data. Afterwards, the permeability study was extended to both biomimetic buccal and skin (STRAT-M®) membranes: with caffeine, biomimetic gastro-intestinal membrane resulted the most permeable (Papp=30.5E-6cm/s), followed by the buccal (Papp=18.2E-6cm/s) and the skin (Papp=0.5E-6cm/s) ones. In a second part of the work, the barrier effect test was developed following a similar permeability-like approach. The protocol was designed with the idea of assessing capacity of a certain product to prevent the passage of caffeine across the biomimetic membrane with respect to a negative and positive control. The untreated membrane was the negative control, while membrane covered with a Vaseline film was the positive one. As last step, the developed barrier effect protocol was applied to an experimental gel-like SB-MD under development for the treatment of aphthae (Aphthae gel, an invented trade name), herein used as a case study. As results, Aphthae gel reduced the caffeine passage of 60.3% thus highlighting its effectiveness to form a protective film. Overall, these results provide important knowledge and may pave the way for the use of these simple but effective biomimetic membranes for carrying out high throughput screening necessary to design safe and effective SB-MD before to proceed further with clinical trials, as requested by the regulation.